Order and compromise : government practices in Turkey - Aymes, Marc; Gourisse, Benjamin; Massicard, Élise (Social, economic, and political studies of the Middle East and Asia., 2015)
Order and Compromise questions the historicity of government practices in Turkey from the late Ottoman Empire onwards. Its discussion of state-society relations reveals how political and administrative institutions are being framed by constant interactions with other social realms.